2017
DOI: 10.3390/ijerph14111359
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Mortality and Disease Attributable to Multiple Air Pollutants in Warsaw, Poland

Abstract: Air pollution is a significant public health issue all over the world, especially in urban areas where a large number of inhabitants are affected. In this study, we quantify the health burden due to local air pollution for Warsaw, Poland. The health impact of the main air pollutants, PM, NOX, SO2, CO, C6H6, BaP and heavy metals is considered. The annual mean concentrations are predicted with the CALPUFF air quality modeling system using the year 2012 emission and meteorological data. The emission field compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…e particulate matter also increases the risk of depressive disorders and suicides [31]. e modelling results indicate that air pollution causes 2800 deaths a year in Warsaw [32]. Moreover, in epidemiological studies conducted in Cracow by Konduracka et al a correlation was found between air pollution with PM 2.5 and the incidence of myocardial infarction [33].…”
Section: Discussionmentioning
confidence: 99%
“…e particulate matter also increases the risk of depressive disorders and suicides [31]. e modelling results indicate that air pollution causes 2800 deaths a year in Warsaw [32]. Moreover, in epidemiological studies conducted in Cracow by Konduracka et al a correlation was found between air pollution with PM 2.5 and the incidence of myocardial infarction [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the Warsaw population, the weighted exposure of NOx is 3.54 μ g/m 3 , PM (2.5)—16.84 μ g/m 3 , Pb—15 ng/m 3 , benzo(a)pyrene—1.95 ng/m 3 , and other metals (As, Cd, Ni)—6.1 ng/m 3 . The degree of pollution strongly depends on which region in Warsaw (with the highest values at the left side of the Vistula River) and what part of the year—with the highest pollution in the winter time [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Air quality in Warsaw is mainly determined by two categories of emission sources, the domestic combustion and the traffic. These are the principal sources of particulate matter (PM), including its fine fraction – PM 2.5 , which is mainly responsible for air pollution-associated mortality ( Wang et al, 2016 ; WHO, 2016 ; Holnicki et al, 2017b ). The coal combustion is the main energy source (electricity/heat) in Poland (85%).…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 2 presents the population density map for Warsaw (Holnicki et al, 2017b), which was compiled on the basis of the home addresses for the same grid as that used in the air quality model. Movement of people was not taken into account.
Fig.
…”
Section: Methodsmentioning
confidence: 99%